Intelligent Flashcards: A Community-Based Education Tool For Fish Consumption Adoption Purposes - Amalia Maulana (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2020)
The conception of this Intelligent Flashcards originates from an attempt to solve the seven tier-based fish consumption barriers in households through community-based education. The method of learning is done through the use of gamification with intelligent flashcards because it is deemed as the easiest method for someone to understand a problem and obtain the most proper solution to it. Educational activities using Intelligent Flashcards may contribute to government efforts in Public Education. It is particularly crucial in areas where the rate of fish consumption is low, so that barriers to fish adoption/consumption may be mitigated through giving each barrier a suitable solution specific to its context. Card games have always been exciting and generate high engagement rates among participants. Utilizing the Intelligent Flashcard, participants were able to understand difficult concepts easier. This method also brings a more pleasant atmosphere during the learning process. The result of the Intelligent Flashcards trial on housewives from lower to middle socioeconomic backgrounds showed there is an increase in the participants' understanding and knowledge to solve challenges they might face regarding fish consumption at home.